EEF1A2 knockdown impairs neuronal proliferation and inhibits neurite outgrowth of differentiating neurons. Issue 8 (20th April 2022) - Rumpansuwon, Kanitin; Prommahom, Athinan; Dharmasaroja, Permphan
Abstract : Objectives: The translation elongation factor-1, alpha-2 (eEF1A2) plays an important role in protein synthesis. Mutations in this gene have been described in individuals with neurodevelopmental disorders. Here, we silenced the expression of eEFA2 in human SH-SY5Y neuroblastoma cells and observed its roles in neuronal proliferation and differentiation upon induction with retinoic acid. Methods: eEF1A2 were silenced using siRNA transfection. Cell proliferation was qualitatively evaluated by Ki-67 immunocytochemistry. Neuronal differentiation was induced with retinoic acid for 3, 5, 7 and 10 days. Neurite length was measured. The expression of microtubule-associated protein 2 (MAP2) was analyzed by western blotting. Tyrosine hydroxylase expression was visualized by immunofluorescence. Cytotoxicity to a neurotoxin, 1-methyl-4-phenylpyridinium (MPP + ), was assessed by the 3-(4, 5-dimethylthiazol-2-yl)-2, 5-diphenyl-2H-tetrazolium bromide (MTT) assay and western blotting of cleaved caspase-3. Results: eEF1A2 knockdown suppressed the proliferative activity of undifferentiated SH-SY5Y cells as shown by decreased Ki-67 immunostaining. Upon retinoic acid-induction, differentiated neurons with eEF1A2 knockdown exhibited shorter neurite length than untransfected cells, which was associated with the reduction of tyrosine hydroxylase and suppression of MAP2 at 10 days of differentiation. eEF1A2 knockdown decreased the survival of neurons, which was clearly observed in undifferentiated and short-term differentiated cells. Upon treatment with MPP +, cells with eEF1A2 knockdown showed a further reduction in cell survival and an increase of cleaved caspase-3 protein. Conclusions: Our results suggest that eEF1A2 may be required for neuronal proliferation and differentiation of SH-SY5Y cells. Increased cell death susceptibility against MPP + in eEF1A2-knockdown neurons may imply the neuroprotective role of eEF1A2.